Child neurology - Menkes, John H., 1928-; Sarnat, Harvey B.; Maria, Bernard L. (Doody's all reviewed collection., 2006)
Revised to incorporate the latest advances in the neurosciences and clinical neurology, the seventh edition of this classic text provides practical, cost-effective problem-solving approaches to all diseases affecting the developing nervous system. In clinically relevant terms, the book explains how recent developments in molecular biology, genetics, neurochemistry, neurophysiology, neuropathology, and neuroimaging impact on diagnosis and treatment. Chapters focus on specific disorders or groups of disorders and emphasize differential diagnosis, disease course, treatment, and prognosis. This ed.